THE ROLE OF PARENTS IN THE INTRODUCTION OF DIGITAL LITERACY IN EARLY CHILDREN - Hendripal Panjaitan; Susanti Nirmalasari; Armanila Armanila; Alfira Damayanti (Proceeding International Seminar of Islamic Studies, 2023)
At this time the advancement of digital technology has influenced parents in educating children. In an all-digital era like this, there are many changes in how to educate parents. In the past, they preferred to play with their children, but now there have been many changes in educating children, for example, it is easier for parents to provide and introduce technology to children on the grounds that children can be quiet and not fussy. This method is recognized by many parents so that their children are not fussy and stay quiet. Digital technology is developing very rapidly at this time of course as parents need to be very clever in introducing digital literacy to early childhood. Because in the current era of digital technology, digital literacy for early childhood is also developing very rapidly.